2020
DOI: 10.1186/s40580-020-00232-9
|View full text |Cite
|
Sign up to set email alerts
|

Laser digital patterning of conductive electrodes using metal oxide nanomaterials

Abstract: As an alternative approach to the conventional deposition and photolithographic processes, the laser digital patterning (LDP) process, which is also known as the laser direct writing process, has attracted considerable attention because it is a non-photolithographic, non-vacuum, on-demand, and cost-effective electrode fabrication route that can be applied to various substrates, including heat-sensitive flexible substrates. The LDP process was initially developed using noble metal nanoparticles (NPs) such as Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 119 publications
(140 reference statements)
0
20
0
Order By: Relevance
“…Laser-based manufacturing techniques have provided the required technological and cost-effective aspects to produce micro-and nanostructures using top-down approaches [75][76][77]. One technique of fabricating periodic structures is LIL [78][79][80][81].…”
Section: Optics-based Ilmentioning
confidence: 99%
“…Laser-based manufacturing techniques have provided the required technological and cost-effective aspects to produce micro-and nanostructures using top-down approaches [75][76][77]. One technique of fabricating periodic structures is LIL [78][79][80][81].…”
Section: Optics-based Ilmentioning
confidence: 99%
“…TCOs are available with a range of different properties. [ 123–126 ] In one particular example of using TCOs for the continuous electrical tuning of metasurfaces, Ge surrounded by Al‐doped ZnO (AZO) was used to produce a reflectance difference of over 40% with gate biases from +4 to −4 V while also displaying a large phase modulation up to 270°. [ 127 ] The devices were modeled using an effective medium theory to calculate the phase shifts.…”
Section: Continuously Tunable Metasurfacesmentioning
confidence: 99%
“…The solution mixture was cast on PET substrates using a stainless-steel coating bar to fabricate large-area, flexible VO 2 (M) films (Figure 12c). The T c of the flexible VO 2 (M) films could be systematically modulated by approximately 24.52 • C for 1 at% of W doping, and the mid-infrared transmission could be modulated by 31% at a T c of 37.3 • C. Inkjet printing has also been widely utilized as a useful direct-write technology to fabricate high-resolution, low-cost, large-area, and uniformsurface films on flexible substrates [141,142]. Haining et al reported the fabrication of VO 2 (M) smart windows via inkjet printing using hydrothermally synthesized VO 2 (M) NPs [143,144].…”
Section: Fabrication Of Flexible Vo 2 (M) Films Through Solution-based Deposition Processmentioning
confidence: 99%